Advances in Bacterial Lysate Immunotherapy for Infectious Diseases and Cancer - Md. Mijanur Rahman; I. Darren Grice; Glen C. Ulett; Ming Q. Wei (Journal of Immunology Research)
Antigenic cell fragments, pathogen-associated molecular patterns, and other immunostimulants in bacterial lysates or extracts may induce local and systemic immune responses in specific and nonspecific paradigms. Based on current knowledge, this review aimed to determine whether bacterial lysate has comparable functions in infectious diseases and cancer treatment. In infectious diseases, including respiratory and urinary tract infections, immune system activation by bacterial lysate can identify and combat pathogens. Commercially available bacterial lysates, including OM-85, Ismigen, Lantigen B, and LW 50020, were effective in children and adults in treating respiratory tract infections, chronic obstructive pulmonary disease, rhinitis, and rhinosinusitis with varying degrees of success. Moreover, OM-89, Uromune, Urovac, Urivac, and ExPEC4V showed therapeutic benefits in controlling urinary tract infections in adults, especially women. Bacterial lysate-based therapeutics are safe, well-tolerated, and have few side effects, making them a good alternative for infectious disease management. Furthermore, a nonspecific immunomodulation by bacterial lysates may stimulate innate immunity, benefiting cancer treatment. “Coley’s vaccine” has been used to treat sarcomas, carcinomas, lymphomas, melanomas, and myelomas with varying outcomes. Later, several similar bacterial lysate-based therapeutics have been developed to treat cancers, including bladder cancer, non-small cell lung cancer, and myeloma; among them, BCG for in situ bladder cancer is well-known. Proinflammatory cytokines, including IL-1, IL-6, IL-12, and TNF-α, may activate bacterial antigen-specific adaptive responses that could restore tumor antigen recognition and response by tumor-specific type 1 helper cells and cytotoxic T cells; therefore, bacterial lysates are worth investigating as a vaccination adjuvants or add-on therapies for several cancers.